The Impact of AI and Reciprocal Symmetry on Organizational Culture and Leadership in the Digital Economy - Maddula, Sai Sirisha (Engineering International, 2018)
The profound effects of reciprocal symmetry and artificial intelligence (AI) on leadership and organizational culture in the digital economy are examined in this study. Examining the impact of AI and reciprocal symmetry integration on leadership styles, workplace ethics, and organizational dynamics are among the main goals. Using a secondary data-based review process, the study synthesizes current literature, research papers, and empirical findings relevant to AI adoption and reciprocal symmetry principles in corporate environments. Significant findings show that AI technologies transform organizational culture, resulting in cultural shifts toward data-driven decision-making, innovation, and cooperation. Principles of reciprocal symmetry promote inclusive environments that highly value openness, justice, and respect for all parties involved. Ethical questions become increasingly important with policy ramifications that demand regulatory frameworks and moral norms to ensure responsible AI deployment and conformity with societal values. This study emphasizes ethical involvement, adaptive leadership, and teamwork when utilizing AI and reciprocal symmetry to promote favorable organizational and social outcomes in the digital economy. Organizations can manage AI adoption while promoting human-centric cultures and long-term value generation by adopting reciprocal symmetry principles.
Keywords: Artificial Intelligence (AI); Reciprocal Symmetry; Organizational Culture; Technological Disruption; Employee Engagement; Innovation; Change Management